New alternatives for the treatment of uncomplicated urinary tract infection, presentation of 2 clinical cases - Andrés F. Reyes; Roberto Ramírez Marmolejo (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2018)
The current perspective on the management of infectious diseases is a challenge for clinicians, because while new antibiotics are developed, bacteria improves its resistance system. That is why this study presents CANTHARIS 9 CH as an alternative treatment for urinary tract infection. This drug has an homeopathic use and it has been tested on humans as an urinary prophylactic. In this text, we present two cases of patients who voluntarily accept to receive this new protocol. Both cases show laboratory confirmation of infection, with quinolone resistance, among others, and negativization post-treatment with CANTHARIS 9 CH. No side effects were reported in this sample.